Prurigo Pigmentosa Induced by Intermittent Fasting and Post-Infectious State in a South Asian Woman: A Diagnostic Dilemma (Bangladesh Journal of Medicine, 2026)
Prurigo pigmentosa is a rare inflammatory dermatosis, often linked to ketosis and dietary changes, and infrequently reported in South Asian populations. The majority of reported cases involve young adults, with a marked female predominance and peak incidence in the second to third decades of life. It presents diagnostic challenges due to its overlap with other papulosquamous and interface dermatoses. Doxycycline is effective for its anti-inflammatory properties and remains a mainstay in treatment. A 34-year-old Pakistani woman developed a pruritic, widespread red brownish scaly itchy rash all over the body for 4 days. There is h/o fever and sore throat 2 weeks ago, no join pain following intermittent fasting and an upper respiratory tract infection. On examination, pruritic erythematous maculopapular eruption with few lesions with scales, began as erythematous purpuric eruption, spreading and turning brownish present all over the body. Histopathology showed parakeratosis, interface dermatitis, and dermal lymphohistiocytic infiltrates with eosinophils features suggestive of prurigo pigmentosa. Differential diagnoses included pityriasis lichenoides et varioliformis acuta (PLEVA) and lichenoid drug reaction. Our plan is to administer symptomatic treatment with emollients, antihistamines, topical steroids and anti-inflammatory. Bilaxtin, Doxycycline for 15 days. The patient responded favourably to doxycycline and symptomatic treatment, with resolution of inflammation and residual hyperpigmentation.This case underscores the need for clinical suspicion of prurigo pigmentosa in patients with dietary or metabolic triggers. Early histopathological confirmation facilitates accurate diagnosis and management.Bangladesh J Medicine 2026; 37(2): 172-175